Xiaoyaosan ameliorates depressive-like behavior and susceptibility to glucose intolerance in rat: involvement of LepR-STAT3/PI3K pathway in hypothalamic arcuate nucleus - Wenqi Qiu; Qian Wu; Kaiwen Zhang; Xiaoli Da; Kairui Tang; Naijun Yuan; Lijuan Deng; Mansi Wu; Ying Zhang; Jiangyan Quan; Qingyu Ma; Xiaojuan Li; et al. (BMC, 2023)
Abstract Background Accumulating evidence has demonstrated that arcuate nucleus (ARC) of the hypothalamus is likely responsible for the close association between chronic stress, depression, and diabetes. Xiaoyaosan (XYS), a Chinese herbal formula, remarkably improves depressive-like behavior and glucose intolerance, but the mechanism remains unclear. Leptin receptor (LepR) regulates energy expenditure and depression by mediating the action of leptin on the ARC. Therefore, we hypothesized that XYS may regulate depressive-like behavior and glucose intolerance via the leptin and its cascade LepR-STAT3/PI3K pathway in the ARC. Methods A rat model of depressive-like behavior and susceptibility to glucose intolerance was induced by exposure to chronic unpredictable mild stress (CUMS) for six weeks. XYS (2.224 g/kg) was orally gavaged for six weeks, and fluoxetine (2.0 mg/kg) was administrated to the positive control group. Depressive-like behaviors were assessed using the open field test (OFT), sucrose preference test (SPT) and forced swim test (FST). Fasting blood glucose (FBG) and oral glucose tolerance test (OGTT) were performed to evaluate the effects of XYS on blood glucose. Peripheral leptin and blood lipids were detected using enzyme-linked immunosorbent assay and an automatic biochemical analyzer, respectively. The effects of XYS on the LepR-STAT3/PI3K pathway were detected by quantitative real-time PCR and western blotting. Results XYS ameliorated CUMS-induced depressive-like behaviors and elevated blood glucose. XYS improved the food intake but have no significant effects on the body weight. Peripheral leptin and its central receptor were also suppressed by XYS, accompanied by the downregulation of JAK2/STAT3 and PI3K/AKT pathway in the ARC. Additionally, XYS increased AGRP and NPY expression but inhibited POMC in the ARC. Conclusions XYS improves depressive-like behaviors and susceptibility to glucose intolerance induced by CUMS, which may be achieved by the downregulation of the LepR-STAT3/PI3K signaling pathway in the ARC.